An assessment of the village tank rehabilitation program of the Freedom From Hunger Campaign Board in Anuradhapura District - Dayaratne, M.H.S.; Moragoda, R. (International Irrigation Management Institute, 1991)
The Village Tank Rehabilitation Program of the National Freedom From Hunger Campaign (FFHC) Board is assessed in this paper as a parallel study to the Anuradhapura Dry-Zone Agriculture Project (ADZAP) which was carried out by the International Irrigation Management Institute (IIMI) in 1988. Following a nongovernmental approach, the FFHC Board has implemented tank rehabilitation programs in several districts in the island. The Thanthirimale cluster in Anuradhapura District is the largest tank rehabilitation project implemented by the Board. In this study, the Board's program in Thanthirimale was assessed through a sample survey, following a similar survey methodology used to assess the Tank Rehabilitation Program of ADZAP